Accounting Students’ Ethical Perceptions of Creative Accounting: The Impact of Intellectual, Emotional, and Spiritual Intelligence - Charly Marlinda; Geaby Desrianti; Muhammad Isa Alamsyahbana (FOUNDAE (Foundation of Advanced Education), 2025)
The increasing number of financial statement manipulation cases in various large companies indicates weakened integrity and ethics in accounting practices. This condition highlights the importance of developing ethical perceptions early in the education process, particularly for accounting students as future professional accountants. The purpose of this study is to analyze the influence of intellectual intelligence, emotional intelligence, and spiritual intelligence on accounting students’ ethical perceptions regarding creative accounting practices. This research employs a quantitative approach with a survey method using a questionnaire. The study population consists of 170 accounting students from the 2020 cohort at STIE Pembangunan Tanjungpinang, with a sample of 63 respondents selected through purposive sampling. Data were analyzed using multiple linear regression with the JASP software. The results indicate that intellectual and spiritual intelligence have a significant effect on students’ ethical perceptions, while emotional intelligence does not have a partial effect. Simultaneously, the three variables significantly influence ethical perceptions of creative accounting practices. These findings suggest that enhancing intellectual and spiritual intelligence can strengthen the professional ethics of future accountants. This study contributes to the development of accounting education grounded in ethical and spiritual values.